A Dynamic Model of Firm Valuation. Issue 3 (15th July 2018) - Lazzati, Natalia; Menichini, Amilcar A.
Abstract: We propose a dynamic version of the dividend discount model, solve it in closed form, and assess its empirical validity. The valuation method is tractable and can be easily implemented. We find that our model produces equity value forecasts that are very close to market prices, and explains a large proportion of the observed variation in share prices. Moreover, we show that a simple portfolio strategy based on the difference between market and estimated values earns considerably positive returns. These returns cannot be simply explained either by the Fama‐French three‐factor model (even after adding a momentum factor) or the Fama‐French five‐factor model.